Seroprevalence of bovine brucellosis in Haryana by avidin-biotin serum ELISA and its comparison with RBPT and SAT - KHURANA, S K; SRIVASTAVA, S K; PRABHUDAS, K (The Indian Journal of Animal Sciences, 2012)
Brucellosis is a zoonotic disease of immense economic importance affecting many species of animals. Serosurveillance of animals from 45 randomly selected villages of 11 districts of Southern Haryana was carried out. Representative serum samples were collected randomly from 5% of the total population of cattle and buffaloes. Overall prevalence of brucellosis was 12.13% (142 cases) out of 1170 serum samples screened by avidin-biotin serum ELISA. It was 14.44% (26 cases) and 11.71% (116 cases) out of 180 cattle and 990 buffalo serum samples, respectively. However, 101(8.6%) and 66 (5.64%) serum samples were found positive by STAT and RBPT, respectively. Prevalence of Brucella antibodies was higher in female animals (16.02% in cattle and 12.32% in buffaloes) than in males (4.14% in cattle and 4.10% in buffaloes). Similarly, sexually mature animals (>3 years of age) were found to be affected more (16.94% in cattle and 13.68% in buffaloes) than the immature ones (